2004
DOI: 10.1177/1094670503260132
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-to-Consumer Conversations in Service Settings

Abstract: This article contributes, in two ways, to our understanding of the nature, scope, and significance of conversations between strangers in service environments. First, a framework is introduced that provides both academics and practitioners with a summary of the key issues associated with the stimuli, manifestations, and consequences of such conversations. Second, the article reports a market-oriented ethnography of a specific service—rail travel—that locates stranger conversations within a broader categorizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 60 publications
(69 reference statements)
7
150
0
3
Order By: Relevance
“…In fact, some authors have already identified C2C behaviours that result in worse service experiences (Grove and Fisk, 1997;Martin, 1996). However, generally, the literature posits that when a positive C2C interaction occurs, such as conversations and handshaking, it results in value for customers (Harris and Baron, 2004). To the authors' best knowledge, only a few studies have focused on the possible negative effects of a positive C2C interaction on customers, and none of the research has addressed social anxiety as an individual trait that could influence the relationship between C2C interaction and value.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, some authors have already identified C2C behaviours that result in worse service experiences (Grove and Fisk, 1997;Martin, 1996). However, generally, the literature posits that when a positive C2C interaction occurs, such as conversations and handshaking, it results in value for customers (Harris and Baron, 2004). To the authors' best knowledge, only a few studies have focused on the possible negative effects of a positive C2C interaction on customers, and none of the research has addressed social anxiety as an individual trait that could influence the relationship between C2C interaction and value.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions among customers in the retail environment are common and can influence the retail experience (Harris and Baron, 2004;Martin, 1996;McGrath and Otnes, 1995). However, C2C interaction occurs not only in physical environments but also in online retail environments, the so-called C2C virtual interaction (Nicholls, 2010).…”
Section: Theoretical Background 21 C2c Interaction and Valuementioning
confidence: 99%
See 1 more Smart Citation
“…It can be argued that event environments and the visitors to that environment (the audience) should not be considered solely as commercial service environments consumed by customers (e.g., as would occur with a nonprofit organization communicating a noncommercial message). The research because the impact of other consumers has shown to be an important factor for the evaluation of the service or experience (Harris & Baron, 2004;Hennig-Thurau, Gwinner, & Gremler, 2002;McAlexander, Schouten, & Koenig, 2002). In hedonic consumption situations (e.g., leisure and tourism settings) consumers are probably more interested in getting social benefits (Levy, 2010;Miao, Mattila, & Mount, 2011).…”
Section: The Social Aspect Of the Event Experiencementioning
confidence: 99%
“…The CCI research focuses on how other consumers sharing the same service environment influence the consumers' experience (Gummesson, 2006;Harris & Baron, 2004). It has been found that other consumers can contribute to satisfaction and enjoyment (Grove & Fisk, 1997;Huang & Hsu, 2010), but also to dissatisfaction (Harris & Reynolds, 2003;Wu, 2007).…”
Section: The Social Aspect Of the Event Experiencementioning
confidence: 99%